PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PADA SISWA SEKOLAH DASAR - Bilqis Waritsa Firdausi; Warsono Warsono; Yoyok Yermiandhoko (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to determine the improvement of critical thinking in elementary school students: a literature review. This study uses a literature study method taken from relevant previous research. Sources of literature studies come from previous research journals with the same research focus (critical thinking skills). The literature study aims to find and analyze some of the efforts that have been made to improve critical thinking skills more quickly and effectively - efficient in learning for elementary school students so that some of these efforts can be applied according to the same conditions in learning. The results in this study obtained as many as 17 journals that were reviewed based on reference sources, sample types, research methods, interventions provided to the results of reviews from journals. The conclusion is that critical thinking skills begin to be trained and developed starting from grade IV/V elementary school. The development of critical thinking skills can be done through the intervention of learning models such as problem-based learning, project-based learning, problem posing, discovery learning, guided inquiry, group investigation; learning approaches such as open-ended, think talk write, realistic, and or the application of games in learning. Critical thinking ability is directly related to student learning outcomes and motivation.